GIS analysis of vulnerabilty from landslides: A case study of Sokobanja municipality - Jovanović Dušica (Zbornik Radova: Geografski Fakultet Univerziteta u Beogradu, 2022)
This paper analyses area endangered by the process of landslides is in the municipality of Sokobanja. The process of landslides is very important from the aspect of environmental protection, considering that it can occur both naturally and under the influence of anthropogenic factors. For the purposes of this analysis data about geological structure, relief characteristics of the terrain (slope, aspect and terrain curvature), distance from rivers, land cover and values of the bare soil index were processed in the GIS environment. The Probability Method (PM) and the Landslide Susceptibility Index (LSI) were used to calculate the predisposition in relation to existing landslides in the study area. The obtained results indicate a high degree of reliability of these statistical methods for landslide prediction.